2021
DOI: 10.2147/dddt.s337524
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Mogroside V on Oxidative Stress Induced by H2O2 in Skin Fibroblasts

Abstract: Purpose Damage caused by oxidative stress leads to the premature aging of cells. Mogrosides, the main active components of Siraitia grosvenorii , have strong antioxidant activity; however, it is unclear whether mogroside V (MV) exerts these effects in skin cells. This was investigated in the present study by evaluating the protective effects of MV against oxidative damage induced by hydrogen peroxide (H 2 O 2 ) in ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Our mogrosides extract was composed of mogrosides IIe, III, IV and V, where the mogroside V was the most abundant in the mixture ( Figure 1 ). Mogroside V is known to have protective effects against oxidative stress in skin fibroblast [ 37 ] and neuronal damages in mice [ 38 ], which supports our gene expression results. Gene expression studies using RT-qPCR indicated that mogrosides up-regulated the expression of oxidative-related genes, including sod-1 ( Figure 4 A), gpx-1 ( Figure 4 B) and clt-1 ( Figure 4 C) in N2 fed with OP50/B12 − , which supports previous research findings regarding the antioxidant properties of mogrosides [ 7 ].…”
Section: Discussionsupporting
confidence: 88%
“…Our mogrosides extract was composed of mogrosides IIe, III, IV and V, where the mogroside V was the most abundant in the mixture ( Figure 1 ). Mogroside V is known to have protective effects against oxidative stress in skin fibroblast [ 37 ] and neuronal damages in mice [ 38 ], which supports our gene expression results. Gene expression studies using RT-qPCR indicated that mogrosides up-regulated the expression of oxidative-related genes, including sod-1 ( Figure 4 A), gpx-1 ( Figure 4 B) and clt-1 ( Figure 4 C) in N2 fed with OP50/B12 − , which supports previous research findings regarding the antioxidant properties of mogrosides [ 7 ].…”
Section: Discussionsupporting
confidence: 88%
“…38 Mogroside V specifically reduces ROS and MDA in H 2 O 2 -treated skin fibroblasts, increasing SOD, GSH-Px, and CAT activities. 39 Additionally, SGP polysaccharide (molecular weight 1.93 × 10 3 kDa) exhibits effective DPPH radical scavenging and reduces ROS and cell damage in H 2 O 2 -damaged PC12 cells in a dosedependent manner. 10 Aging and Ovarian Function: Aging, marked by a decline in bodily functions, 40 particularly affects the ovaries, which show significant functional decline after 35 years.…”
Section: ■ Health Benefits and Mechanism Of Actionmentioning
confidence: 99%
“…Meanwhile, mogroside V ( 16 ) promotes the anti-oxidative stress capacity of skin fibroblasts by modulating the scavenging of free radicals with antioxidant enzymes, which could be used to prevent skin aging or lesions. In MSF treated with H 2 O 2 , mogrosides V ( 16 ) reduced ROS levels and MDA content, together with an increase in superoxide dismutase (SOD), glutathione peroxide (GSH-Px), and catalase (CAT) activities [ 47 ]. Furthermore, mogroside extracts (MGE) inhibited BSA glycation, as evidenced by the formation of fluorescent advanced glycation end products (AGEs) at 500 μg/ml with lower levels of protein carbonate and Ne-(carboxymethyl) lysine.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%